Morpho-Molecular Study and Biochemical Management of Fusarium Solani in Bell Pepper - Khan, Muhammad Arslan; Riaz, Hasan; Ramzan, Muhammad; Ullah, Unsar Naeem; Ali, Haider; Ishfaq, Tooba (BioScientific Review, 2023)
Bell pepper (Capsicum annum L.) is one of the most important vegetable crops in Pakistan. This crop is prone to many fungal diseases, such as Phytophthora blight, Fusarium wilt, Verticillium wilt, Powdery mildew, and Anthracnose. Among all of them, Fusarium wilt is the most devastating disease of bell pepper that is responsible for heavy yield reduction. This study is aimed to identify and manage Fusarium solani in bell pepper, in vitro as well as in pots experiment. For this purpose, sampling, isolation, purification, and morpho-molecular identification were performed. Molecular characterization of F. solani was achieved by using ITS primers. The results showed that the nucleotide sequence of these isolates showed 100% homology to Fusarium solani. In vitro management was done by the application of Trichoderma harzianum and synthetic fungicides (Thiophanate methyl, Mancozeb+Metalaxyl, Fosetyl aluminum, Difenoconazole, and Sulphur). Five concentrations (100 ppm, 200 ppm, 400 ppm, 800 ppm, and 1000 ppm) were employed using dual culture and food poisoning method, respectively. LSD was used in combination with four replications. Data was taken after 3, 5, 7, and 10 days. The results showed that T. harzianum inhibited F. solani growth up to 87.98% after 10 days. As compared to the biological treatment, Thiophanate methyl showed maximum inhibition (100%) after 3 days at 100 ppm. Later on, its efficacy at 100 ppm was reduced after 5, 7, and 10 days. The inhibition after 10 days was calculated to be 72.89%. At 200, 400, 800, and 1000 ppm, the percentage of inhibition was up to 100%. Furthermore, Mancozeb + Metalaxyl showed maximum inhibition (100%) after 3 days at 1000 ppm. Similarly, Fosetyl aluminum showed maximum inhibition (100%) after 3 days at 1000 ppm. Whereas, Difenoconazole showed maximum inhibition (100%) after 3 days at 800 ppm. Later on, the efficacy at 800 ppm was reduced after 7 and 10 days. The inhibition after 10 days was calculated to be 87.72%. At 1000 ppm, the percentage of inhibition was up to 100%. Finally, sulphur showed maximum inhibition 82.7% after 3 days at 1000 ppm. Later on, its efficacy at 1000 ppm was reduced after 5, 7, and 10 days. The inhibition after 10 days was calculated to be 62.62%.